Cigarette butts, a threat for marine environments: Lessons from benthic foraminifera (Protista). (December 2020) - Caridi, Francesca; Sabbatini, Anna; Birarda, Giovanni; Costanzi, Elisa; De Giudici, Giovanni; Galeazzi, Roberta; Medas, Daniela; Mobbili, Giovanna; Ricciutelli, Massimo; Ruello, Maria Letizia; Vaccari, Lisa; Negri, Alessandra
Abstract: Cigarette butts are the most common form of litter in the world and their environmental impact is related to both persistence and potential toxic effects for chemical composition. The objective of this study was to assess the acute toxicity (LC50 -48 h) of human-smoked cigarette butts leachate on 3 cultured genera of benthic foraminifera: the calcareous perforate Rosalina globularis, the calcareous imperforate Quinqueloculina spp., and the agglutinated Textularia agglutinans. The specimens were exposed to 16, 8, 4, 2, and 1 cigarette butts/L concentrations that prove to be acutely toxic to all taxa. Starting from 4 cigarette butts/L, both calcareous genera showed shell decalcification, and death of almost all the individuals, except for the more resistant agglutinated species. These results suggest the potential harmfulness of cigarette butts leachate related to pH reduction and release of toxic substances, in particular nicotine, which leads to physiology alteration and in many cases cellular death. Highlights: Cigarette butts' leachates induces acute toxicity in benthic foraminifera. Agglutinated species are more resistant to cigarette butts leachate than calcareous species. Chemical substances and pH reduction are responsible for decalcifying and dissolution processes and cellular death.